Influence of saturable absorber parameters on the operation regimes of a dumbbell-shaped thulium fibre laser. (June 2021) - Zverev, A.D.; Kamynin, V.A.; Trikshev, A.I.; Kovtun, E.Yu.; Arutyunyan, N.R.; Mastin, A.A.; Ryabochkina, P.A.; Obraztsova, E.D.; Tsvetkov, V.B.
Abstract: The influence of saturable absorber parameters on the operation regimes of a dumbbell-shaped thulium fibre laser is studied. As saturable absorbers, polymer films with nanotubes characterised by different transmission coefficients in the saturated and unsaturated states are used. The operation of lasers with absorbers of different configurations used to obtain stable Q -switching and mode-locking regimes in the spectral range 1930 – 1960 nm is demonstrated. The average output power in the single-pulse mode-locking regime is 3.5 mW at a pulse repetition rate of 8.4 MHz and a pulse duration of 1.08 ps.